Detectability of hydrous minerals using ONC-T camera onboard the Hayabusa2 spacecraft. Issue 7 (1st October 2015) - Kameda, S.; Suzuki, H.; Cho, Y.; Koga, S.; Yamada, M.; Nakamura, T.; Hiroi, T.; Sawada, H.; Honda, R.; Morota, T.; Honda, C.; Takei, A.; et al.
Abstract: The Hayabusa2 spacecraft has three framing cameras (ONC-T, ONC-W1, and ONC-W2) for optical navigation to asteroid 1999 JU3 . The ONC-T is a telescopic camera with seven band-pass filters in the visible and near-infrared range. These filters are placed on a wheel, which rotates to put a selected filter for different observations, enabling multiband imaging. Previous ground-based observations suggesting that hydrous materials may be present on the surface of 1999 JU3 and distributed in relatively limited areas. The presence of hydrous minerals indicates that this asteroid experienced only low to moderate temperatures during its formation, suggesting that primordial materials are preserved. In order to find the best sampling sites, we will perform reflectance spectroscopic observations using the ONC-T near the asteroid after arrival. Finding regions rich in hydrous minerals is the key for this remote sensing observation. In preparation for this, we conducted ground-based experiments for the actual ONC-T flight model to confirm the detectability of the absorption band of Fe-rich serpentine. As a result, we detected the absorption band near 0.7 μm by reflectance spectroscopy of CM2 chondrites, such as Murchison and Nogoya, which are known to contain the Fe-rich serpentine, and did not detect any 0.7 μm absorption in Jbilet Winselwan CM2 chondrite with decomposed Fe-rich serpentine.